EFFECT OF RESOURCE CONSERVING TECHNOLOGIES ON SOIL QUALITY INDICES UNDER RICE-WHEAT CROPPING SYSTEM - KAUR, AMRIT; TALATAM, SATYANARAYANA; CHAUDHARY, ANITA; Kaur, AMRJEET (Annals of Agricultural Research, 2014)
The study was undertaken to determine the effect of Resource conserving technologies (RCTs) viz., zero tillage (ZT) and bed planting (BP) over conventional tillage (CT) on different soil quality indicators under the rice-wheat cropping system. Out of 16 soil properties measured, 13 were statistically different (P